Evaluasi Pelaksanaan Redistribusi Tanah Eks Kawasan Hutan di Kabupaten Musi Rawas - Agung Anugra Putra Dempo; M Nazir Salim; Abdul Haris Farid (Sekolah Tinggi Pertanahan Nasional, 2021)
In 2019, Musi Rawas Regency carried out land redistribution on ex-forest land. The issuance of Presidential Regulation Number 86 in 2018 is expected to accelerate the implementation of agrarian reform. This regulation requires the provision of technical standards, institutional, and stage of activity that run in ideal condition. Therefore, it is necessary to conduct research to explain the extent of the suitability of that components applied in its implementation. This research uses qualitative method and descriptive approach. The result of this research are in the form of mechanism for change of status of forest area through forest area inauguration and the implementation of that land redistribution is carried out according to procedure. Constraints encountered include the relinquishment of the forest area which is still at the official report of the boundary setting area which is still at the official report of the boundary setting stage, the revision of land use plan (RTRW) is still in progress, and some administrative deficiencies can be resolved appropriately with good coordination between that stakeholders involved.Pada tahun 2019, Kabupaten Musi Rawas melaksanakan redistribusi tanah dari tanah eks kawasan hutan. Terbitnya Peraturan Presiden Nomor 86 Tahun 2018 diharapkan dapat mempercepat pelaksanaan reforma agraria. Regulasi ini mensyaratkan adanya standar teknis, kelembagaan, dan tahapan kegiatan yang berjalan dalam kondisi ideal. Oleh karena itu perlu dilakukan penelitian untuk menjelaskan sejauh mana kesesuaian komponen tersebut diterapkan dalam pelaksanaanya. Penelitian ini menggunakan metode kualitatif dengan pendekatan deskriptif. Hasil penelitiannya menunjukkan bahwa mekanisme perubahan status kawasan hutan dilakukan dengan pengukuhan kawasan hutan dan pelaksanaan redistribusi tanah tersebut dilaksanakan sesuai prosedur. Kendala-kendala yang ditemui, yakni pelepasan kawasan hutan yang baru sampai pada tahap berita acara tata batas, revisi Rencana Tata Ruang Wilayah (RTRW) sedang berjalan, dan beberapa kekurangan kelengkapan administrasi yang seharusnya bisa diselesaikan dengan tepat dengan koordinasi yang baik antara stakeholder yang terlibat